Google App Engine Java and GWT application development - Guermeur, Daniel; Unruh, Amy. (Birmingham : Packt Pub., 2010)
In Detail Google Application Engine is a cloud computing technology that lets you run web applications that are easy to build and maintain as well as being scaled and load-balanced automatically. To build interesting and interactive web applications developers are turning to Java. However, building and deploying scalable web applications using Google Web Toolkit and Google App Engine for Java can be challenging even to developers. The start to finish approach of this book helps you meet these challenges. This book is designed to give developers all the information they need to develop their own GAE+GWT applications, with a particular focus on some of the technologies useful for building scalable social-media-oriented applications. It is an easy-to-follow guide that shows you how to get the most out of combining the powerful features of GAE and GWT. It provides you with solutions to many of the problems that arise in developing, maintaining, and scaling web applications. The book introduces you to the features of Google App Engine (GAE) and the Google Web Toolkit (GWT) to help you build interesting and interactive real-world AJAX applications. Over the course of the book, you are guided by the development of a sample application using the Google Web Toolkit (GWT) plugin for Eclipse. To make things easier for you, all application building blocks are explained in detail, walking you through the development process step by step. The book teaches you the key technologies and methodologies that can be applied to developing your application locally, enhancing your application functionality and accelerating performance, integrating your application with Google Accounts, Facebook, and Twitter as well as monitoring and maintaining your web application. Packed with great examples and clear explanations, you will be able to build your own web applications that are scalable and reliable using GAE and GWT with Java. Build a real-world interactive web application in the cloud using GAE/J and GWT, with Push, background processing, OAuth, social media APIs, and moreApproach This is a practical guide with a step-by-step approach that builds an application in stages. Each stage of the application is used along with screenshots to introduce or develop your understanding of how to write powerful GAE applications. Who this book is for If you are a developer with prior programming experience of Java development and object-oriented programming and want to understand the key concepts of how to build AJAX web applications with Java, then this book is for you. The book assumes some previous exposure to the basics of using GWT, for example at the level of Google's online introductory GWT tutorials. You don't need to know anything about Google App Engine. This book will teach you everything you need.
Includes index.
Print version record.
Added to collection customer.56279.3
Keywords: Google Apps; Google Apps; Application software; Logiciels d'application.; COMPUTERS -- Web -- Web Programming; Application software